2017
DOI: 10.18282/jsd.v2.i2.90
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the role of subcision suction method with and without the injection of platelet-rich plasma in the treatment of depressed scars

Abstract: Among wound-healing modalities, platelet-rich plasma (PRP) has been used for wound healing, through the release of multiple growth factors. The platelets mediate wound healing by initiating the clotting pathway and the subsequent matrix remodelisation. The aim of the work was to study the role of injection of platelet-rich plasma in the treatment of scars. This study was conducted on thirty patients who were divided into two groups (A and B). Each group included fifteen patients. The two groups were randomly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…In our survey of the etiologies of scars, most patients had a history of acne leading to atrophic scars, accounting for 90%; only 6.7% of patients had post-varicella scars; and 3.3% had traumatic scars. According to Nouran Abd El, Aziz Abou Khedr, et al (2017), the cause of atrophic scars is mainly acne, accounting for 80%, and chicken pox, accounting for 10%, 6% due to trauma, and 4% due to surgery [1]. Thus, the results of the above study are similar to ours.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our survey of the etiologies of scars, most patients had a history of acne leading to atrophic scars, accounting for 90%; only 6.7% of patients had post-varicella scars; and 3.3% had traumatic scars. According to Nouran Abd El, Aziz Abou Khedr, et al (2017), the cause of atrophic scars is mainly acne, accounting for 80%, and chicken pox, accounting for 10%, 6% due to trauma, and 4% due to surgery [1]. Thus, the results of the above study are similar to ours.…”
Section: Discussionsupporting
confidence: 86%
“…Scars result from a natural healing process that leads to the formation of fibrous tissue that replaces normal tissue destroyed by injury or disease [1]. Scar formation can result in keloid scarring due to increased fibrous tissue formation, but more commonly, atrophic scars are formed due to tissue loss or reduction at the site of injury [2].…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that combining PRP therapy with fractional resurfacing resulted in a rise in dermal elasticity and collagen thickness as well as a decrease in erythema [11] . Combining PRP with fractional lasers or subcision suction to treat atrophic acne scars has been shown to shorten the healing time, as well as to diminish erythema and edema, while encouraging keratinocyte, fibroblast, and collagen proliferation [12][13][14] . There might be some side effects when using PRP that the patient must be aware of before the procedure.…”
mentioning
confidence: 99%